Factors Influencing the Development of Mild Cognitive Impairment in Community-Dwelling People Aged 75 Years and Older - Akio Goda; Shin Murata; Kayoko Shiraiwa; Teppei Abiko; Hideki Nakano; Koji Nonaka; Hiroaki Iwase; Kunihiko Anami; Yuki Kikuchi; Jun Horie (Geriatrics, 2021)
In Asia, including Japan, dementia incidence peaks in older adults over ≥75 years; it is therefore important to detect mild cognitive impairment (MCI), and prevent its onset in this age group. Our study hypothesized that physical and psychological status would be associated with MCI incidence among community-dwelling people aged 75 years and older. The study population comprised 291 such individuals. Participants with a Mini-Mental State Examination score of 28 or more were considered non-MCI, and those with a score of less than 28 and greater than 24 were considered to have MCI. Several other measures were also evaluated, including information about their current medical visits due to diseases, depressive symptom severity, various physical functions (trunk function, 30 s chair-stand test, one-legged stance test, timed up and go test time, 5 m walking time, grip strength, knee-extension strength, and toe-grip strength), and body composition (body fat and skeletal muscle mass). Participants suspected of having MCI had significantly shorter educational histories, higher rates of medical visits due to hypertension, and poorer balance abilities. The results suggest that these indices can be considered screening indicators for detecting MCI in people aged 75 years and older, which may be useful for planning intervention programs for this population.